Harnessing Memory NK Cell to Protect Against COVID-19 - Soleimanian, Saeede; Yaghobi, Ramin (Frontiers in Pharmacology, 2020)
The worldwide struggle against the coronavirus disease 2019 (COVID-19) as a public health crisis continues to sweep across the globe. Up to now, effective antiviral treatment against COVID-19 is not available. Therefore, throughout virus infections, a thorough clarification of the virus-host immune system interactions will be most probably helpful to encounter these challenges. Emerging evidence suggests that just like SARS and MERS, COVID-19 primarily suppresses the innate immune system, enabling its stable propagation during the early stage of infection. Consequently, proinflammatory cytokines and chemokines have been increasing during infection progression associated with severe lung pathology. It is imperative to consider hyper inflammation in vaccine designing, as vaccine-induced immune responses must have a protective role against infection without leading to immunopathology. Among the front-line responders to viral infections, Natural Killer (NK) cells have immense therapeutic potential, forming a bridge between innate and adaptive responses. A subset of NK cells exhibits putatively increased effector functions against viruses following pathogen-specific and immunization. Memory NK cells have higher cytotoxicity and effector activity, compared with the conventional NK cells. As a pioneering strategy, prompt accumulation and long‐term maintenance of these memory NK cells could be an efficacious viral treatment. According to the high prevalence of human cytomegalovirus (HCMV) infection in the world, it remains to be determined whether HCMV adaptive NK cells could play a protective role against this new emerging virus. In addition, the new adaptive-like KIR+NKG2C+ NK cell subset (the adaptive-like lung tissue residue (tr)NK cell) in the context of the respiratory infection at this site could specifically exhibit the expansion upon COVID-19. Another aspect of NK cells we should note, utilizing modified NK cells such as allogeneic off-the-shelf CAR-NK cells as a state-of-the-art strategy for the treatment of COVID-19. In this line, we speculate introducing NKG2C into chimeric antigen receptors in NK cells might be a potential approach in future viral immunotherapy for emerging viruses. In this contribution, we will briefly discuss the current status and future perspective of NK cells, which provide to successfully exploit NK cell-mediated antiviral activity that may offer important new tools in COVID-19 treatment.